2019
DOI: 10.1021/acs.molpharmaceut.9b00713
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Lipid–Dendrimer Hybrid Nanoparticles: An Approach To Target and Eliminate Intracellular Pathogens

Abstract: pH-responsive drug delivery systems are yielding opportunities to directly deliver antibiotics to the site of infection. Therefore, this study aimed to develop and evaluate novel pH-responsive lipid−dendrimer hybrid nanoparticles (LDH-NPs) for the delivery of vancomycin (VCM) to the site of infection, by intracellular bacterial pathogens. The LDH-NPs were formulated using the emulsification solvent evaporation method and were characterized by various in vitro and molecular dynamic (MD) simulation techniques. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 119 publications
0
24
0
Order By: Relevance
“…The hemolytic activity assay to assess the hemolytic behavior of the VCM-StBAclm-Qt1 quatsomes was performed according to a previously reported method [ 41 , 42 ]. Fresh whole sheep blood (100 μL) was added to a freshly prepared PBS pH 7.4 (1 mL) containing 50, 100, 150, 200, and 250 µg of VCM-loaded StBAclm-Qt1 quatsomes.…”
Section: Methodsmentioning
confidence: 99%
“…The hemolytic activity assay to assess the hemolytic behavior of the VCM-StBAclm-Qt1 quatsomes was performed according to a previously reported method [ 41 , 42 ]. Fresh whole sheep blood (100 μL) was added to a freshly prepared PBS pH 7.4 (1 mL) containing 50, 100, 150, 200, and 250 µg of VCM-loaded StBAclm-Qt1 quatsomes.…”
Section: Methodsmentioning
confidence: 99%
“…Exosomes modified with rabies viral glycoprotein (RVG), which is a viral protein that interacts with the murine p75 neurotrophin receptor, have been used in an experimental mouse model reducing neuropathological disorders associated with Parkinson's disease. [ 148 ]…”
Section: Exosomes As Drug Delivery Systemsmentioning
confidence: 99%
“…Exosomes modified with rabies viral glycoprotein (RVG), which is a viral protein that interacts with the murine p75 neurotrophin receptor, have been used in an experimental mouse model reducing neuropathological disorders associated with Parkinson's disease. [148] Also, central nervous system (CNS) -derived exosomes can transport amyloidogenic proteins that play an important role in several neurodegenerative diseases, such as Alzheimer's disease. In addition, CNS-derived exosomes can cross the blood brain barrier (BBB) and appear in the blood, meaning that they can be used as biomarkers of neurodegenerative diseases produced in the CNS.…”
Section: Exosomes For Neurological Diseasesmentioning
confidence: 99%
“…Recently, dendrimers decorated with positively charged amino acids on the superficial were synthesized [70]. Recently, Govender et al [71] formulated and evaluated novel pH-responsive lipid-dendrimer hybrid nanoparticles for the targeted delivery of vancomycin in the site infection. The study has shown that the pH-responsive release of nanoparticle enhanced antibacterial efficacy and intracellular delivery as antibiotic.…”
Section: Nano-sizementioning
confidence: 99%